2012
DOI: 10.3109/09273972.2012.680234
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Abnormalities and Systemic Disease in Down Syndrome

Abstract: Comorbidities are common in DS and complicate diagnosis, development, and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…Thicker macular structure may be a primary pathology related to the disorder. Stirn et al reported the presence of foveal hypoplasia or retinal pigment epithelium hyperplasia in 32.2 % of patients with Down syndrome [29]. Our data showed that thickening could result from both inner and outer layers, which agrees with this report.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Thicker macular structure may be a primary pathology related to the disorder. Stirn et al reported the presence of foveal hypoplasia or retinal pigment epithelium hyperplasia in 32.2 % of patients with Down syndrome [29]. Our data showed that thickening could result from both inner and outer layers, which agrees with this report.…”
Section: Discussionsupporting
confidence: 95%
“…Although there are published reports discussing these issues, much of the current data are considerably variable. For example, Stirn et al noted that among a total of 65 Down syndrome children who visited their hospital, 32 % suffered from abnormalities of the retinal vessels, foveal hypoplasia, or retinal pigment epithelium hyperplasia [29]. Fimiani et al, however, reported retinal anomalies in only 6 % of 157 Italian children with Down syndrome [30].…”
Section: Introductionmentioning
confidence: 97%
“…Astigmatism was 71.0%~84.8% in the children aged under 10 years, and over 90% in subjects in their late teens, that is, higher than that in the previous reports. Reportedly, the percentage of astigmatism ranges from 19 to 72.4 5,6,8,10,14,18–20,22,24,25. However, the percentages in those studies were not even, as the standard value of the definition of astigmatism was not constant.…”
Section: Discussionmentioning
confidence: 98%
“…However, the percentages in those studies were not even, as the standard value of the definition of astigmatism was not constant. High astigmatism, defined as more than 2.0D and 3.0D, has reportedly ranged from 29% to 59% 5,6,14,20. In this study, the mean values were 1.5~2.2 DC and the percentage of astigmatism defined as more than 2.0D was from 33 to 64.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation